Karakteristik Sensori Kopi Robusta Berdasarkan Tingkat Kematangan Buah - Budi Hartoyo (Jurnal Agrifoodtech, 2023)
Coffee is one of the leading commodities in the plantation subsector in Indonesia which can compete in quality globally, so coffee has a strategic role in the national economy. Until now, coffee demand shows a positive trend, not only domestic demand but also global demand, which is increasing at a rate of 14% increase in coffee consumption every year. Coffee is an agricultural product that relies on quality and taste aspects. The quality and taste of coffee is influenced by many factors, one of which is the level of ripeness of the fruit at harvest time. Improper harvesting will affect the quality and taste of the coffee, for this reason it is necessary to test the sensory characteristics of Robusta Coffee based on the level of fruit ripeness. The research used a Completely Randomized Design (CRD) with three (3) treatments based on the composition of fruit maturity levels, namely 95% red fruit + 5% green fruit (M1); 85% red fruit + 15% green fruit (M2); and 75% red fruit + 25% green fruit (M3). The testing method used is a cupping test which follows SCA (Specialty Coffee Association) rules with 20 semi-trained panelists. Based on the Robusta coffee cupping test, the highest total score of 78.86 was obtained from a composition of 95% red fruit + 5% green fruit (M1), followed by a composition of 85% red fruit + 15% green fruit (M2) with a total score of 77.57. , and the lowest in the composition of 75% red fruit + 25% green fruit (M3) with a total score of 71.38. The results of the panelists' assessment of Robusta coffee at various maturity level compositions are still not included in specialty coffee.